Green Accounting in Environmental Disclosure and Corporate Social Responsibility Perspective in Indonesia - Citradewi, Adelina (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
The modern era is characterized by technological developments followed by increasing environmental problems. Many of these problems arise from human activities to gain profit. The implementation of green accounting is carried out in the form of environmental activities in terms of costs and benefits to increase the efficiency of environmental management. This study examines how the implementation of green accounting in developing countries, such as Indonesia. This type of research is descriptive research with a quantitative approach. The population used in this study are all companies listed on the Indonesia Stock Exchange (IDX) in the period 2012 to 2021. The sampling technique uses purposive sampling so that 28 companies are obtained each year. The results of the study prove that out of 12 items of disclosure of environmental information, only 3 items of the disclosure that have a value of mode 5, namely: (1) Information regarding steps or ways to reduce the environmental impact of the products and/or services produced; (2) Information on measurable commitments to reduce dependence on renewable or non-renewable resources; (3) Information regarding waste disposal and recycling. In addition, there are 3 disclosure items have a value of mode 1, namely: (1) Information about initiatives to provide efficient energy or renewable energy; (2) Accounting for waste and pollution from the company's operating activities; and (3) Significant fines and non-monetary sanctions for non-compliance.